Power Generation Potential of Small Wind Turbine in Elazig Province, Turkey - Yildiz, Ahmet; Dandil, Besir (Ieee, 2019)
As an alternative to fossil fuels, wind energy is a clean, environmentally friendly and renewable energy source. In the design of wind energy conversion systems, the wind speed of the region is one of the most important parameters and the economic applicability of wind power generation depends on the wind speed. In this study, the feasibility of small scale wind turbine is investigated for Elazig province in the east of Turkey. For this purpose, the average wind speeds on a monthly basis of Elazig province for ten years were taken into consideration. Wind speed measurements were done both for December, which the average wind speed was the lowest in 2018 and for March, which the average wind speed was the highest in 2018 and the results were evaluated. The power energy potential that can be generated of the three-bladed small type wind turbine designed according to these data has been determined. In addition, in order to observe the effect of turbine installation height on wind speed, wind speeds were calculated at different installation heights and the effect of these values on the power generation potential of the designed small type wind turbine was determined. As a result, it was observed that small type wind turbines can be used for generate electricity in low speed regions. In case of wind turbine installed at a height of 50 m, it is observed that it is possible to generate significant amounts of electrical energy with small wind turbines in Elazig and these turbines can be a technically applicable option for power generation.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: Elazig province; power generation potential; small wind turbine; wind speed